An Introduction to automata theory and formal languages - Pandey, Adesh Kumar (S.K.Kataria, 2005)
An Introduction to automata theory and formal languages / Pandey, Adesh Kumar. -- Delhi: S.K.Kataria, 2005 006.3 P189e2 2nd ed No. of Copies : 1